Decision Support System Determination of Recipients Subsidized Fertilizer Donation Using the SMART (Simple Multi Attribute Rating Technique) - Eric Alfonsius; Stephano W. C. Ngangi; Aditya Lapu Kalua (Journal of Information Technology, Software Engineering and Computer Science, 2023)
The decision support system to determine recipients of subsidized fertilizer subsidies is a decision support system application that can process data to determine recipients of subsidized fertilizer subsidies. The purpose of this study is to create an information system that can identify beneficiaries of subsidized fertilizer grants. The existence of this system can optimize the provision of subsidized fertilizers to farmers who really need these fertilizers. In its application, this study uses existing research methods such as data collection techniques, observation and documentation methods, as well as testing methods using the black box testing method to test the functionality of the program / website to be created with a success percentage reaching 100% compared to existing excel calculations and researchers make qualitative testing with Likert scale testing for the level of acceptance of applications made where The Likert scale test results tested gave results of 86.27% with a very good research success rate. Therefore, this research is said to be successful so that it can be used as a basis for the implementation of decision support systems in existing research sites.